Thermodynamic analysis of gravity assisted solar-powered reverse osmosis unit for greenhouses situated in a depleted zone - Yasser M. Abdullatif (14151324) (2021)
The Sabkha-Tah region of Western Sahara is a location where adverse weather conditions make it difficult for the conventional farming of certain crops. However, the region is uniquely situated in a depleted zone 60 m below sea-level. In this unique energy, water, and food nexus study, an analysis of a novel multi-generation system that harnesses the surrounding geography to produce power, cooling, and freshwater for a greenhouse situated in the Sabkha-Tah region is performed. The system utilises the Atlantic Ocean's hydrostatic pressure to decrease the power consumption of the reverse osmosis (RO) water desalination unit. A solar-powered Rankine cycle is used to meet the energy demands of the RO and absorption cooling units. A thermodynamic analysis of the system is performed, and the results demonstrate that the use of an energy recovery turbine along with the geographical advantage of the region decreased the power requirement of the RO unit. The system demonstrates that 46.18 kW of energy can be saved when using the water's hydrostatic pressure. The net power consumption in the RO unit is 226 kW, and it can provide 90 m3/h of freshwater. The energy required to produce 1 m3 of freshwater is 2.51 kWh, and the overall energy and exergy efficiencies for the multi-generation system are calculated to be 60.8% and 29.76%, respectively. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2021.100990